A Study of Buddhadāsa Bhikku’s Concept of Death Before Death of Death Before Death การศึกษาเรื่องการตายก่อนตายตามทัศนะของพุทธทาสภิกขุ - Kanjanapisarn, Supree (วารสารรามคำแหง ฉบับมนุษยศาสตร์, 2014)
Abstract From ancient times, death is the mysterious problem that surrounds all human beings. In Buddhist teaching, death can be overcome by facing the fact and understanding the body as the composition of five aggregates, not self and one can free oneself from all attachment by practicing the eightfold path. This article proposes the concept of “death before death” known as the end of attachment to the idea of ‘I’ and ‘mine’ by Buddhadāsa Bhikkhu as a way for bringing people away from materialism and a practice for achieving the extinction of all defilements and suffering in this life of here and now. The aim of this article is to study the real meaning of death (maraṇa), to analyze and criticize the concept of “death before death” of Buddhadāsa Bhikkhu which is related to the supreme goal of Buddhism (nibbāna) and also compare his demythologization and his own hermeneutic method with the teaching as appeared in the Buddhist texts by using the descriptive and comparative method to reflect the idea of anthropology, sociology and phenomenology of religion and scholars for building the bridge of intra-faith and interfaith dialogues among people of different religions. บทคัดย่อ ตั้งแต่สมัยโบราณมา ความตายถือเป็นเรื่องลึกลับที่รายล้อมมนุษย์ทุกคน พระพุทธศาสนา สอนว่า ความตายสามารถเอาชนะได้โดยการเผชิญหน้ากับความจริงนี้ และมีความเข้าใจว่าร่างกายเป็นเพียงขันธ์ห้าไม่ใช่ตัวตน และบุคคลสามารถคลายการยึดมั่นถือมั่นได้โดยการปฏิบัติตามอริยมรรคแปด บทความนี้เป็นการเสนอแนวคิดเรื่องตายก่อนตายที่กล่าวถึงการตายจากความยึดมั่นถือมั่นในตัวกูของกู และวิธีการปฏิบัติต่อความตายของพุทธทาสภิกขุว่าเป็นคำสอนของศาสนาที่จะนำมนุษย์ออกมาจากวัตถุนิยมและเป็นวิธีปฏิบัติเพื่อเข้าถึงความสิ้นกิเลสและทุกข์ทั้งปวงที่นี่และเดี๋ยวนี้ บทความนี้มีจุดมุ่งหมายเพื่อศึกษาความหมายที่แท้จริงของความตายเพื่อวิเคราะห์และแสดงความคิดเห็นต่อแนวคิดเรื่องตายก่อนตายของพุทธทาสภิกขุซึ่งเชื่อมโยงกับเป้าหมายสูงสุดของพระพุทธศาสนาคือพระนิพพาน กับทั้งเปรียบเทียบการให้ความหมายในเชิงตรรกะและวิธีการตีความของพุทธทาสภิกขุกับคำสอนที่ปรากฏในคัมภีร์พุทธศาสนาโดยใช้วิธีการพรรณนาและเปรียบเทียบเพื่อสะท้อนถึงแนวคิดเชิงมานุษยวิทยา สังคมวิทยาและปรากฏการณ์วิทยาทางศาสนาผ่านมุมมองของพุทธทาสภิกขุและนักวิชาการอื่นเพื่อสร้างสะพานเชื่อมความสัมพันธ์อันดีระหว่างบุคคลในศาสนาเดียวกันและต่างศาสนา